Peripheral multimodal monitoring of ANS changes related to epilepsy - Vieluf, Solveig; El Atrache, Rima; Hammond, Sarah; Touserkani, Fatemeh Mohammadpour; Loddenkemper, Tobias; Reinsberger, Claus (Epilepsy & Behavior)
Keywords: Behavioral Neuroscience; Neurology (clinical); Neurology

26. Regionalgeschichtstagung: Tafeln und Speisen, Essen und Schlemmen – regional oder global? - Duschner, Paul (Paderborner Historische Mitteilungen)

Vom Sammeln und Ausstellen ostasiatischer Kunst: das Beispiel des Ehepaars Adolf und Frieda Fischer - Duschner, Paul (Paderborner Historische Mitteilungen)

Experimentelle Untersuchung einse modifzierten Nasspressverfahrens für die Herstellung von hybriden Metall-Faserverbundkunststoff-Bauteilen - Opdemom, Hermann
Das Nasspressverfahren ist ein Serienherstellungsprozess für Bauteile aus duroplastischen Faserverbundkunststoffen (FVK) mit einer geringen Geometriekomplexität. Im Rahmen dieser Arbeit wurde ein modiﬁziertes Nasspressverfahren untersucht, welches die Herstellung von hybriden Blech-FVK-Strukturen ermöglicht. Die stoffschlüssige Verbindung zwischen dem metallischen Trägerbauteil und einem lokalen FVK-Verstärkungselement wird durch Co-Bonding im Nasspresswerkzeug aufgebaut. Epoxidbasierte Matrixharze und Klebstoffe wurden mit Methoden der Klebtechnik sowie thermischen und rheometrischen Prüfungen charakterisiert, um ein materialspeziﬁsches Fertigungsprozessfenster einzugrenzen. Experimentelle Untersuchungen zum Nasspressen von GFK-Laminaten und Stahl-GFK-Hybridstrukturen fokussierten die Mikrostruktur und das strukturelle Verhalten von stoffschlüssigen Hybridverbindungen. Unter anderem wurden Einﬂüsse von zeit-, temperatur- und druckabhängigen Fertigungsparametern sowie der Einsatz von Strukturklebstoffﬁlmen und internen Trennmitteln analysiert. Anhand von Fallturmtests an hybriden Demonstratorkomponenten konnte das modiﬁzierte Nasspressverfahren für die Herstellung crashrelevanter Karosseriebauteile qualiﬁziert werden.
Keywords: Leichtbau; Faserverbundkunststoffe; Nasspressverfahren; Hybridbauteile; Rheologie; Klebtechnik; Co-Bonding

Experimental Basis for an Orthotropic Failure Model for Application in Crash Simulation - Stolzenburg, Marc Patrick
Um das Verhalten von Strukturen frühzeitig im Entwicklungsprozess mittels numerischer Simulationen vorhersagen zu können, ist eine genaue Beschreibung der Materialeigen-schaften notwendig. Diese Arbeit fokussiert sich auf das orthotrope Versagen von hoch- und ultrahochfesten Stahlblechen. Das Materialverhalten wurde u.a. mittels optischer Dehnungsmessung untersucht und zeigte eine Abhängigkeit von dem Belastungszustand und der Probenorientierung. Zudem wurde für einen ausgewählten hochfesten Stahl der Einfluss der Materialdicke auf das Materialverhalten bestimmt.Auf Basis der lokalen Dehnungen wurde die plastische Instabilität, definiert als Beginn der makroskopischen Schädigung, experimentell bestimmt. Mittels der lokalen Dehnungen und eines Plastizitätsmodells wurden die Lastpfade der untersuchten Proben ermittelt, die Belastungszustände bei Versagen bestimmt und die Versagenskurven des Materialmodells definiert.Anhand der experimentellen Ergebnisse wurden die Materialien orthotrop charakterisiert. Um den Einfluss der Orthotropie zu bestimmen, wurde eine Robustheitsanalyse durchgeführt. Mittels der Materialmodelle konnte das Verhalten der Proben vorhergesagt werden. Allerdings zeigte das orthotrope Materialmodell einen nur geringen Einfluss auf das untersuchte Bauteil der Robustheitsanalyse.

Laserinduzierte Nanostrukturierung intrinsisch gefertigter Hybridstrukturen – Oberflächenmorphologie, Verbindungs- und Korrosionseigenschaften - Zinn, Carolin

Theoretical description of a multimode SU(1,1) interferometer - Ferreri, A.; Sharapova, P.; Luo, Kai Hong; Herrmann, H.; Silberhorn, C. (Quantum Information and Measurement (QIM) V: Quantum Technologies)
Keywords: pc2-ressources

Generating two-mode squeezing and Schrödinger cat states with multimode measurement-induced nonlinearity - Riabinin, Matvei; Sharapova, Polina; Bartley, Tim; Meier, Torsten
Keywords: pc2-ressources

Temporally multimode four-photon Hong-Ou-Mandel interference - Ferreri, Alessandro; Ansari, V.; Silberhorn, Christine; Sharapova, Polina R. (Physical Review A)

Transferprozesse bei mehrsprachigen Literacy-Erfahrungen. - Topalović, Elvira (Sprachenvielfalt als Ressource begreifen. Mehrsprachigkeit in bilingualen Kindertagesstätten und Schulen.)

Entanglement swapping with photons generated on-demand by a quantum dot - Basset, F. Basso; Rota, M. B; Schimpf, C; Tedeschi, D; Zeuner, K.D; Covre da Silva, S.F; Reindl, M; Zwiller, V; Jöns, Klaus D.; Rastelli, A; Trotta, R

Dephasing free photon entanglement with a quantum dot - Fognini, A; Ahmadi, A; Zeeshan, M; Fokkens, J.T; Gibson, S.J; Sherlekar, N; Daley, S.J; Dalacu, D; Poole, P.J; Jöns, Klaus D.; Zwiller, V; Reimer, M.E

Resonance fluorescence of GaAs quantum dots with near-unity photon indistinguishability - Schöll, E; Hanschke, L; Schweickert, L; Zeuner, K.D; Reindl, M; Covre da Silva, S.F; Lettner, T; Trotta, R; Finley, J.J; Müller, K; Rastelli, A; Zwiller, V; et al.

Reconfigurable Frequency Coding of Deterministic Single Photons in the Telecom C-Band - Gyger, S; Zeuner, K.D; Jöns, Klaus D.; Elshaari, A.W; Paul, M; Popov, S; Reuterskiöld Hedlund, C; Hammar, M; Ozolins, O; Zwiller, V

Entwicklung eines Vorgehens zum Safety Assessment für sicherheits-kritische Informationssysteme in der zivilen Gefahrenabwehr am Beispiel der Feuerwehr - Schäfer, Christina

Teilautomatisierte Parameteridentifikation für die Validierung von Dynamikmodellen im modellbasierten Entwurf mechatronischer Systeme - Kruse, Daniel

Adaptive Finite Element Methods for Direct and Inverse Problems in Nonlinear Solid Mechanics - Widany, Kai-Uwe

Experimental Characterization and Constitutive Modeling of Reinforced Thermoplastic and Thermosetting Polymers - Damman, Christian

Adaptive Methods in the Mechanics of Heterogeneous Materials - Ju, Xiaozhe

Secure State Estimation Against Integrity Attacks: A Gaussian Mixture Model Approach Secure State Estimation Against Integrity Attacks: A Gaussian Mixture Model Approach - Guo, Z.; Shi, D.; Quevedo, D. E.; Shi, L. (Trans. Signal Processing)

A multi-mechanism model for cutting simulations combining asymmetric effects and gradient phase transformations - Cheng, Chun

Musikstadt Riga im europäischen Kontext. Deutsch- lettische Wechselbeziehungen im 19. und 20. Jahrhundert. Bericht über das Symposion Riga 3.–4. Oktober 2014. - Tumat, Antje (Die Musikforschung)

Katherine K. Wong: Music and Gender in English Renaissance Drama - Tumat, Antje (Jahrbuch für Musik und Gender)

Computationally Efficient Modelling and Precision Position and Force Control of SMA Actuators - Pai, Arathi

Hanley, Catherine, Matilda, Empress, Queen, Warrior - Foerster, Anne (Francia Recensio)

Optimierungsstrategien für Strukturbauteile mittels additiver Fertigungsverfahren - Brüggemann, Jan-Peter

Almost Optimal Classical Approximation Algorithms for a Quantum Generalization of Max-Cut - Gharibian, Sevag; Parekh, Ojas (Proceedings of the 22nd International Workshop on Approximation Algorithms for Combinatorial Optimization Problems (APPROX))

The complexity of simulating local measurements on quantum systems - Gharibian, Sevag; Yirka, Justin (Quantum)

Numerische und experimentelle Untersuchungen zur Aerosolbildung aus binären Dampfgemischen von Wasser und Glycerin - Zhen, Xinz

Computing quadratic subfields of number fields - Elsenhans, Andreas-Stephan; Klüners, Jürgen (arXiv:1907.13383)
Given a number field, it is an important question in algorithmic number theory to determine all its subfields. If the search is restricted to abelian subfields, one can try to determine them by using class field theory. For this, it is necessary to know the ramified primes. We show that the ramified primes of the subfield can be computed efficiently. Using this information we give algorithms to determine all the quadratic and the cyclic cubic subfields of the initial field. The approach generalises to cyclic subfields of prime degree. In the case of quadratic subfields, our approach is much faster than other methods.

Entwicklung einer Methode zur Vorhersage der ertragbaren Kraft einschnittig überlappter FVK-Stahl-Klebverbindungen unter Berücksichtigung von Faserarchitektur, Faserorientierung und Matrixsystem - Henkel, Katharina

Weiterentwicklung der Stanzniettechnologie für das werkstoffgerechte Fügen von FKV-Metall-Verbindungen - Augenthaler, Florian

Auslegung von elastischen Klebverbindungen unter klimatischer Wechselbeanspruchung - Mailänder, Sebastian

Ein Beitrag zum mechanischen Fügen von hochmanganhaltigen TWIP-Stählen - Matzke, Marcus

Rereading Marx in the Age of Digital Capitalism - Fuchs, Christian

Untersuchung alternativer Sensoren und Datenanalysemethoden für Schraubprozesse - Röske, Jonathan

Untersuchungen zu kontinuums- und bruchmechanischen Methoden für die Prognose des Crashverhaltens toleranzbehafteter Strukturklebverbindungen - Bobbert, Mathias

Modellierung und numerische Simulation gekoppelter Transportprozesse in Strukturelementen kleinskaliger Destillationsverfahren für binäre Zweiphasensysteme - Rieks, Sebastian

Ein Beitrag zur kombinierten (quasi-)statischen und dynamischen Umformung von blechförmigen Halbzeugen - Djakow, Eugen

Simulationsgestützte Analyse und Optimierung der Umformung geschlossener Stahlprofile mittels Hamburger Verfahren - Tabakajew, Dmitri

Digital Objects, Digital Subjects: Interdisciplinary Perspectives on Capitalism, Labour and Politics in the Age of Big Data

Henri Lefebvre’s Theory of the Production of Space and the Critical Theory of Communication - Fuchs, Christian (Communication Theory)

Öffentlichkeit im digitalen Kapitalismus - Fuchs, Christian (Das Ende der Vielfalt? Zur Diversität der Medien)

Social Media, Big Data, and Critical Marketing - Fuchs, Christian (The Routledge Companion to Critical Marketing)

Appropriation of Digital Machines and Appropriation of Fixed Capital as the Real Appropriation of Social Being: Reflections on Toni Negri’s Chapter - Fuchs, Christian (Digital Objects, Digital Subjects: Interdisciplinary Perspectives on Capitalism, Labour and Politics in the Age of Big Data)

M. N. Roy and the Frankfurt School: Socialist Humanism and the Critical Analysis of Communication, Culture, Technology, Fascism and Nationalism - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

What is Critical Digital Social Research? Five Reflections on the Study of Digital Society - Fuchs, Christian (Journal of Digital Social Research)

We Need a Full Public Service Internet – State-Owned Infrastructure is Just the Start - Fuchs, Christian (The Conversation)

Boris Johnson Takes His Brexit Demagoguery to the Social Media Sphere - Fuchs, Christian (TruthOut)

重读马克思:资本主义批判与激进理论的未来[J] - Fuchs, Christian; Monticelli, Lara (国外理论动态 (Foreign Theoretical Trends) 2019 (8))

Critical Theory of Communication: New Readings of Lukács, Adorno, Marcuse, Honneth and Habermas in the Age of the Internet (Chinese translation) - Fuchs, Christian

Revisiting the Althusser/E. P. Thompson-Controversy: Towards a Marxist Theory of Communication - Fuchs, Christian (Communication and the Public)

Straightforward Immobilization of Phosphonic Acids and Phosphoric Acid Esters on Mesoporous Silica and Their Application in an Asymmetric Aldol Reaction - Weinberger, Christian; Heckel, Tatjana; Schnippering, Patrick; Schmitz, Markus; Guo, Anpeng; Keil, Waldemar; Marsmann, Heinrich C.; Schmidt, Claudia; Tiemann, Michael; Wilhelm, René (Nanomaterials)
The combined benefits of moisture-stable phosphonic acids and mesoporous silica materials (SBA-15 and MCM-41) as large-surface-area solid supports offer new opportunities for several applications, such as catalysis or drug delivery. We present a comprehensive study of a straightforward synthesis method via direct immobilization of several phosphonic acids and phosphoric acid esters on various mesoporous silicas in a Dean–Stark apparatus with toluene as the solvent. Due to the utilization of azeotropic distillation, there was no need to dry phosphonic acids, phosphoric acid esters, solvents, or silicas prior to synthesis. In addition to modeling phosphonic acids, immobilization of the important biomolecule adenosine monophosphate (AMP) on the porous supports was also investigated. Due to the high surface area of the mesoporous silicas, a possible catalytic application based on immobilization of an organocatalyst for an asymmetric aldol reaction is discussed.

Phase Transitions of Ice in Aqueous Salt Solutions within Nanometer-Sized Pores - Jantsch, Evelyn; Weinberger, Christian; Tiemann, Michael; Koop, Thomas (The Journal of Physical Chemistry C)
We examined the effect of CaCl2 and LiCl on ice melting in mesoporous silica (MCM-41 and SBA-15 silica). For that purpose, we determined the ice melting temperature in pores of various size (pore radii between 1.9 and 11.1 nm) in water and aqueous solutions up to high total solute molality (up to about 12 mol kg–1) using differential scanning calorimetry. We found that both electrolytes reduce the ice melting temperature within the pores. An exception is the melting of ice in the smallest pores, which does not seem to be affected by the presence of solutes, most likely owing to an exclusion of the ions from entering the pores. For all other pores, we observed that the ice melting temperature decreases as a function of pore size and electrolyte concentration. Using thermodynamic considerations as well as additional experimental data we developed a parametrization that can be used to predict the ice melting point as a function of pore size and total solute molality. For that purpose, we extended a formulation of the effective water activity of aqueous solutions under mechanical pressure toward its application in confinement and tested this new parametrization on literature data.

Textile Transformationen: Die "Frau comme il faut" in der robe à transformation und die "Tempofrau" im Verwandlungskleid - Kraft, Kerstin

Laufsteg Museum. Über Modeausstellungen und Ausstellungsmoden - Kraft, Kerstin

Kulturelle Zyklographie der Dinge - Kraft, Kerstin

Phase Coupling of Bilateral Motor Areas Decreases from Bipedal to Single Leg Stance - Lehmann, Tim; Büchel, Daniel; Cockcroft, John; Abegail Louw, Quinette; Baumeister, Jochen

Social Media and Everyday Politics - Allmer, Thomas (Concept: The Journal of Contemporary Community Education Practice Theory)

Academic Labour, Digital Media and Capitalism - Allmer, Thomas (Critical Sociology)

Kritická teorie a sociální média: Mezi emancipací a komodifikací. Translated - Allmer, Thomas

Whitepaper Künstliche Intelligenz und Diskriminierung – Herausforderungen und Lösungsansätze - Matzner, Tobias; Beck, Susanne; Grundwald, Armin; Jacob, Kai (der Plattform Lernende Systeme)

Sinnvoll versus gesund? – Bestimmungen der Mediennutzung - Matzner, Tobias (Gehirn & Geist Nr. 1 (2019))

Plural, situated subjects in the critique of artificial intelligence - Matzner, Tobias (The Democratization of Artificial Intelligence – Net Politics in the Era of Learning Algorithms)

Challenging algorithmic profiling: The limits of data protection and anti-discrimination in responding to emergent discrimination - Mann, Monique; Matzner, Tobias (Big Data & Society)
The potential for biases being built into algorithms has been known for some time (e.g., Friedman and Nissenbaum, 1996), yet literature has only recently demonstrated the ways algorithmic profiling can result in social sorting and harm marginalised groups (e.g., Browne, 2015; Eubanks, 2018; Noble, 2018). We contend that with increased algorithmic complexity, biases will become more sophisticated and difficult to identify, control for, or contest. Our argument has four steps: first, we show how harnessing algorithms means that data gathered at a particular place and time relating to specific persons, can be used to build group models applied in different contexts to different persons. Thus, privacy and data protection rights, with their focus on individuals (Coll, 2014; Parsons, 2015), do not protect from the discriminatory potential of algorithmic profiling. Second, we explore the idea that anti-discrimination regulation may be more promising, but acknowledge limitations. Third, we argue that in order to harness anti-discrimination regulation, it needs to confront emergent forms of discrimination or risk creating new invisibilities, including invisibility from existing safeguards. Finally, we outline suggestions to address emergent forms of discrimination and exclusionary invisibilities via intersectional and post-colonial analysis.

Autonome Trolleys und andere Probleme. Konfigurationen Künstlicher Intelligenz in ethischen Debatten über selbstfahrende Kraftfahrzeuge - Matzner, Tobias (Zeitschrift für Medienwissenschaft)

Privatsphäre 4.0. Eine Neuverortung des Privaten im Zeitalter der Digitalisierung - Behrendt, Hauke; Loh, Wulf; Matzner, Tobias; Misselhorn, Catrin

Self-aligned organic thin-film transistors for flexible electronics - Meyers, Thorsten; Reker, Julia; Temme, Julian; Vidor, Fábio F.; Hilleringmann, Ulrich (Fifth Conference on Sensors, MEMS, and Electro-Optic Systems)

Inorganic p-channel thin-film transistors using CuO nanoparticles - Reker, Julia; Meyers, Thorsten; Vidor, Fábio F.; Hilleringmann, Ulrich (Fifth Conference on Sensors, MEMS, and Electro-Optic Systems)

Gas Responsive Nanoswitch: Copper Oxide Composite for Highly Selective H2S Detection - Paul, Andrej; Schwind, Bertram; Weinberger, Christian; Tiemann, Michael; Wagner, Thorsten (Advanced Functional Materials)
A nanocomposite material based on copper(II) oxide (CuO) and its utilization as a highly selective and stable gas-responsive electrical switch for hydrogen sulphide (H2S) detection is presented. The material can be applied as a sensitive layer for H2S monitoring, e.g., in biogas gas plants. CuO nanoparticles are embedded in a rigid, nanoporous silica (SiO2) matrix to form an electrical percolating network of low conducting CuO and, upon exposure to H2S, highly conducting copper(II) sulphide (CuS) particles. By steric hindrance due to the silica pore walls, the structure of the network is maintained even though the reversible reaction of CuO to CuS is accompanied by significant volume expansion. The conducting state of the percolating network can be controlled by a variety of parameters, such as temperature, electrode layout, and network topology of the porous silica matrix. The latter means that this new type of sensing material has a structure-encoded detection limit for H2S, which offers new application opportunities. The fabrication process of the mesoporous CuO@SiO2 composite as well as the sensor design and characteristics are described in detail. In addition, theoretical modeling of the percolation effect by Monte-Carlo simulations yields deeper insight into the underlying percolation mechanism and the observed response characteristics.

Nanoparticles and organic semiconductors for flexible electronics - Hilleringmann, Ulrich; Reker, Julia; Vidor, Fábio F.; Meyers, Thorsten; Joubert, Trudi H.; Bezuidenhout, Petroné (Fifth Conference on Sensors, MEMS, and Electro-Optic Systems)

Improved organic thin-film transistor performance by dielectric layer patterning - Temme, Julian; Meyers, Thorsten; Reker, Julia; Vidor, Fábio F.; Vollbrecht, Joachim; Kitzerow, Heinz; Paradies, Jan; Hilleringmann, Ulrich (Fifth Conference on Sensors, MEMS, and Electro-Optic Systems)

Mechanical deformation on nanoparticle-based thin-film transistors - Vidor, Fabio Fedrizzi; Meyers, Thorsten; Reker, Julia; Müller, Kathrin; Wirth, Gilson I.; Hilleringmann, Ulrich (Fifth Conference on Sensors, MEMS, and Electro-Optic Systems)

Oxygen detection with zinc oxide nanoparticle structures - Schwabe, Tobias; Balke, Axel; Bezuidenhout, Petrone; Reker, Julia; Meyers, Thorsten; Joubert, Trudi-Heleen; Hilleringmann, Ulrich (Fifth Conference on Sensors, MEMS, and Electro-Optic Systems)

Characterization of inkjet-printed dielectric on different substrates - Kruger, Jené; Bezuidenhout, Petroné H.; Hilleringmann, Ulrich; Joubert, Trudi-Heleen (Fifth Conference on Sensors, MEMS, and Electro-Optic Systems)

Method of superposing a multiple driven magnetic field to minimize stray fields around the receiver for inductive wireless power transmission - Lange, Sven; Bueker, Maik-Julian; Sievers, Denis; Hedayat, Christian; Foerstner, Jens; Hilleringmann, Ulrich; Otto, Thomas (Smart Systems Integration; 13th International Conference and Exhibition on Integration Issues of Miniaturized Systems)

Characterization of H-field Probes regarding Unwanted Field Suppression using Different Calibration Structures - Schroeder, Dominik; Hangmann, Christian; Hedayat, Christian; Otto, Thomas; Hilleringmann, Ulrich (Smart Systems Integration; 13th International Conference and Exhibition on Integration Issues of Miniaturized Systems)

Wireless power supply for a RFID based sensor platform - Schmidt, Marco; Petrov, Dmitry; Hedayat, Christian; Hilleringmann, Ulrich; Otto, Thomas (Smart Systems Integration; 13th International Conference and Exhibition on Integration Issues of Miniaturized Systems)

Characterization of inkjet-printed dielectric on different substrates - Kruger, Jené; Bezuidenhout, Petroné H.; Hilleringmann, Ulrich; Joubert, Trudi-Heleen (Fifth Conference on Sensors, MEMS, and Electro-Optic Systems)

RFID based sensor platform for industry 4.0 application - Petrov, Dmitry; Schmidt, Marco; Hilleringmann, Ulrich; Hedayat, Christian; Otto, Thomas (Smart Systems Integration; 13th International Conference and Exhibition on Integration Issues of Miniaturized Systems)

Devolopment, Production and post-processing of a topology optimized aircraft bracket - Klippstein, Sven Helge; Duchting, Anne; Reiher, Thomas; Hengsbach, F.; Menge, Dennis; Schmid, Hans-Joachim (30th Annual International Solid Freeform Fabrication Symposium)
Structural parts for aviation have very high demands on the development and production process. Therefore, the entire process must be considered in order to produce high-quality AM metal parts. In this case study, a conventional part was selected to be optimized for AM. The process presented includes component selection, design improvement with a novel approach for topology optimization based on the AMendate algorithm as basis of MSC Apex Generative Design,component production on a SLM 250 HL and post-processing including heat treatment and surface smoothing. With the topology optimization a weight reduction of ~60 % could be realized, whereby the stress distribution is more homogeneous. Furthermore, the challenges of support optimization and post-processing have to be addressed, in order to produce competitive parts.

Einfache Ermittlung von Schnellhärtungsparametern für elementar geklebte Strukturen - Ditter, Jan; Aubel, Tobias; Teutenberg, Dominik; Meschut, Gerson (adhäsion KLEBEN & DICHTEN)
Keywords: Polymers and Plastics; General Chemical Engineering; General Chemistry

Joining of high strength aluminum alloys by refill friction stir spot welding (III-1854-18) - Schmal, Christopher; Meschut, Gerson; Buhl, Nico (Welding in the World)
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Zwei Betrachtungen von Sicherheit und Privatheit nach Snowden - Auerbach, Benedikt; Shnayien, Mary; Kiltz, Eike; Tuschling, Anna (Datenschutz und Datensicherheit - DuD)
Was verstehen wir heute, sechs Jahre nach den Snowden-Leaks, unter IT-Sicherheit und Privatheit in digitalen Kulturen? Dieser Frage gehen Benedikt Auerbach aus kryptographischer und Mary Shnayien aus medienwissenschaftlicher Perspektive nach. So beschäftigt sich Benedikt Auerbach mit dem Skalierungsverhalten kryptographischer Verfahren. Es beschreibt, inwiefern sich Angriffe auf einzelne Nutzerinnen und Nutzer des Verfahrens zugroßskaligen Angriffen auf zahlreiche Nutzerinnen und Nutzer übertragen lassen – ein für Massenüberwachung durch Geheimdienste relevantes Angriffsszenario. Mary Shnayien untersucht ausgehend von der weltweiten Cyberattacke WannaCry diskursanalytisch, wie IT-Sicherheit zum Forschungsgegenstand und -feld wurde, und welche Metaphern das Feld strukturieren.

History and Aesthetics of Progress Indicators [Edistymispalkkien historia ja estetiikka] - Raczkowski, Felix; Shnayien, Mary (Tekniikan Waiheita)

Transformation und Wandel der Beruflichen Integrationsförderung. Vom „Erfolgsmodell“ zum „Problemfall“. - Heisler, Dietmar (Berufsbildung. Zeitschrift für Theorie-Praxis-Dialog)
Der Beitrag skizziert in einem historischen Exkurs zentrale Entwicklungslinien der beruflichen Benachteiligtenförderung. Es wird deutlich, dass gesellschaftliche Veränderungen zu einer deutlich kritischeren und pädagogisch reflektierten Sicht auf berufliche Fördermaßnahmen geführt haben.
Keywords: Benachteiligtenförderung; Transformation

Potentiale und Herausforderungen von multiprofessionellen Teams aus systemischer Perspektive. - Engemann, Mario; Aßmann, Sandra; Bührmann, Thorsten

Kooperation zwischen Schulen und außerschulischen Bildungspartnern. Eine empirische Untersuchung zu Potenzialen und Herausforderungen von multiprofessionellen Teams am Beispiel des Projektes ‚Lebenswelten aktiv gestalten‘ - Engemann, Mario

Spatially asymmetric transients of propagating exciton-polariton modes in a planar CdZnTe/CdMgTe guiding structure - Vondran, J.; Spitzer, F.; Bayer, M.; Akimov, I. A.; Trautmann, Alexander; Reichelt, Matthias; Meier, Cedrik; Weber, N.; Meier, Torsten; André, R.; Mariette, H. (Physical Review B)

Marita Jendrischewski: Carl Schmitz – Vom Webstuhl in die Namib. Die Lebensgeschichte eines bergischen Missionars, Remscheid 2018 - Schroeter-Wittke, Harald (Jahrbuch für Evangelische Kirchengeschichte des Rheinlandes)

Jutta Krauß / Ulrich Kneise: Welterbe Wartburg. Porträt einer Tausendjährigen, Regensburg 2016 - Schroeter-Wittke, Harald (Jahrbuch für Evangelische Kirchengeschichte des Rheinlandes)

Friedl Brunckhorst / Karl Weber (Hg.): Kaiser Wilhelm II. und seine Zeit, Regensburg 2016 - Schroeter-Wittke, Harald (Jahrbuch für Evangelische Kirchengeschichte des Rheinlandes)

Schire Jaakow und Weihnachtsidylle. Zum 100. Todestag von Alfred Rose - Schroeter-Wittke, Harald (Praktische Theologie)

Das neue Evangelische Gesangbuch – eine Phantasie - Schroeter-Wittke, Harald (Liturgie und Kultur)

Go down, Moses! Zum 75. Todestag von Robert Nathaniel - Schroeter-Wittke, Harald (Praktische Theologie)

Tod-Verweigerung. Zum 75. Todestag von Viktor Ullmann - Schroeter-Wittke, Harald (Praktische Theologie)

Rilkes Stunden-Buch. Ein Triptychon – neu - Schroeter-Wittke, Harald (Praktische Theologie)

Antje Mickan / Thomas Klie / Peter A. Berger (Hg.): Räume zwischen Kunst und Religion. Sprechende Formen und religionshybride Praxis (Rerum Religionum. Arbeiten zur Religionskultur 1), Bielefeld 2019 - Schroeter-Wittke, Harald (Kunst und Kirche)

Larissa Eikermann / Stefanie Haupt / Roland Linde / Michael Zelle (Hgg.), Die Externsteine. Zwischen wissenschaftlicher Forschung und völkischer Deutung, Münster 2018 - Schroeter-Wittke, Harald (Jahrbuch für Westfälische Kirchengeschichte)

Holger Pyka: Protestantische Karnevalsrezeption und Transformationen konfessioneller Mentalität. Stuttgart 2018 - Schroeter-Wittke, Harald (Jahrbuch der Hessischen Kirchengeschichtlichen Vereinigung)